THE EFFECT OF USING FLASHCARDS ON STUDENT VOCABULARY MASTERY - Riryn Fatmawaty (Universitas Islam Lamongan, 2016)
As we know that vocabulary is as a major component of language learning. Without having adequate vocabulary we will get difficulty to learn English. So that way it has to be mastered by learners. It should be the first priority in English language teaching and learning because as a central of language teaching and learning. It means that by mastering vocabulary, of course with grammar, the learners will produce so many sentences easily either in spoken or written one. Actually, there are many methods that used by teacher in English's teaching in order to reach the goal in teaching and learning English, such as using cartoon movies, pictures, jigsaws, games, song and etc. Another way is learning through vocabulary card or flashcard. As we listen and read, we often meet new words by flashcard. A flashcard is a set of cards bearing information, as words or numbers, on either or both sides, used in classroom drills or in private study